Consensus in the Islamic Legal System - Zakyi Ibrahim (International Institute of Islamic Thought, 2016)
All Muslims regard the Qur’an as authoritative. The Sunnah, on the other hand, although authoritative to the majority of Muslims, does not enjoy such universality.1Yet to the Sunnis and Shi‘ahs, both of them are so authoritative that they are unquestionable sources of Islamic legal system. Thus, they are sources “from” which Islamic law is directly derived. So what makes “consensus” (ijmā‘: whether of the Muslim community or of the scholars) such a compelling candidate for an additional source of the legal system as far as Sunnis are concerned? I contend that (1) the early jurists viewed this as the safest way to inoculate and safeguard that system (and the other sources) from individual abuse and personal manipulation and that (2) without consensus and why it was originally construed and framed (notwithstanding how it was applied) by the jurists, the Qur’an and the Sunnah (despite their inherent religious and theological authority) would be meaningless or inadmissible as legitimate sources of law. But before I discuss consensus, I would like to address the two authoritative sources of law. All Muslims accept the Qur’an as God’s own words and therefore as the main source of the legal system (fiqh). Before the jurists began to deliberate and codify fiqh, the Shari‘ah was already embedded in the Qur’an and Muslims were living their socio-religious and politico-economic lives in accordance with its teachings. Therefore, when the jurists were ready to put the laws into written form, they located all its original rules and expounded upon them. However, universal recognition differs from universal agreement on the meaning of specific injunctions. In addition, it certainly differs from the claim that the Qur’an covers every foreseeable legal injunction, for it does not. For a variety of reasons, the the Sunnah, does not enjoy any universal authority, among them (1) Some Muslims have questioned how the Prophet’s teachings have been preserved and passed on, (2) classical and modern scholars have raised serious doubts about the authenticity of certain hadiths, and ...